Desarrollo rural sostenible metodologías para el diagnóstico microrregional. Revisión de Literatura - Sepulveda Sergio (Instituto Interamericano de Cooperación Agrícola (IICA), 2019)
This publication is an extensive bibliographic review of diverse methodological approaches to partially manage a few dimensions of a spatial diagnosis. Nonetheless, the work concentrates mostly upon those references published during the last several years in latin america, the caribbean, the U.S., and Canada. This asessment permitted the confirmation of the hypothesis formulated at the outset of this undertaking